Lia Salgado (1914-1980): trajetória artística e contribuição para a canção brasileira de câmara - Raquel Giesbrecht Calais (2021)
This dissertation had as its research object the artistic trajectory of the soprano Lia Salgado (1914-1980), an outstanding figure in the development of musical production in Minas Gerais since the foundation of Cultura Artística de Minas Gerais, Sociedade Mineira de Concertos Sinfônicos, Sociedade Coral de Belo Horizonte and Universidade Mineira de Arte. Data about her engagement as an interpreter and disseminator of the Brazilian Art Song, for which she dedicated several 78 rpm and LPs recordings were addressed. We also present data on two scores dedicated to the artist, namely, Saudade by Pedro de Castro (18951978) and Canção da retirante by Carlos Alberto Pinto Fonseca (1933-2006). With this research, we hope to contribute to the dissemination of the Brazilian Art Song and to register Lia Salgado’s outstanding performance as an interpreter and historical figure in the development of the history of Brazilian music since 1950s.